Altman Z-Score Analysis To Predict Bankruptcy In The Food Industry Industry In Indonesia In 2018-2022 - Nardi Sunardi; Ardhi febriansyah; Raden Taufik Nur Hidayat (Indonesian Development of Economics and Administration Journal, 2023)
This research aims to assess the extent of corporate insolvency using the Altman Z-Score model in the Food Industry, specifically focusing on companies listed on the Indonesia Stock Exchange from 2018 to 2022. The selection criteria for the sample involved companies that consistently published financial reports during the aforementioned period. The findings of this study demonstrate that the Altman Z-Score model can effectively identify the likelihood of bankruptcy in the Food Industry listed on the Indonesia Stock Exchange. For companies classified as susceptible to bankruptcy, it is crucial for them to exercise caution when formulating corporate policies and strive to enhance overall company performance. They should also endeavor to optimize the utilization of their assets to attain maximum profitability. On the other hand, companies in a financially stable condition should maintain and enhance their performance in generating profits to avoid bankruptcy.